The Relationship Between Trust and Truth and Reconciliation Commissions in Post-Conflict Sub-Saharan Countries - Keil, Julie; Stegbauer, Alexander (Advances in Social Sciences Research Journal, 2020)
Sub-Saharan African countries have conducted Truth and Reconciliation Commissions (TRC) from the early 1970’s to 2020 in twenty-one different countries. TRCs have been chosen by states after armed conflicts, attempted or completed coups or in several cases after contested elections and election violence, in attempt to agree at a common “truth” to the events and to bring reconciliation to individual victims and polarized groups within the state. Most TRCs have claimed the need to build trust in institutions, government and communities as one of the reasons for the conduct of a TRC. However, despite extensive scholarly study of TRCs in general, and some study of sub-Saharan African TRCs (particularly the South African TRC) there is a lack of study of the relationship between TRCs and the development of trust. This study utilizes Afrobarometer data regarding trust in various governmental and quasi-governmental entities in ten Sub-Saharan African states that conducted a TRC. This study concludes that the processes in strong TRCs are related to the improvement in trust in some of the entities, but others are unaffected or show decreases in trust because the processes generally used in the TRC were not effective in creating trust.